Mobile Stroke Units: Current and Future Impact on Stroke Care - Bowry, Ritvij; Grotta, James C. (Seminars in Neurology, 2021)
Ischemic stroke is a leading cause of death and major disability that impacts societies across the world. Earlier thrombolysis of blocked arteries with intravenous tissue plasminogen activator (tPA) and/or endovascular clot extraction is associated with better clinical outcomes. Mobile stroke units (MSU) can deliver faster tPA treatment and rapidly transport stroke patients to centers with endovascular capabilities. Initial MSU trials in Germany indicated more rapid tPA treatment times using MSUs compared with standard emergency room treatment, a higher proportion of patients treated within 60 minutes of stroke onset, and a trend toward better 3-month clinical outcomes with MSU care. In the United States, the first multicenter, randomized clinical trial comparing standard versus MSU treatment began in 2014 in Houston, TX, and has demonstrated feasibility and safety of MSU operations, reliability of telemedicine technology to assess patients for tPA eligibility without additional time delays, and faster door-to-groin puncture times of MSU patients needing endovascular thrombectomy in interim analysis. Scheduled for completion in 2021, this trial will determine the cost-effectiveness and benefit of MSU treatment on clinical outcomes compared with standard ambulance and hospital treatment. Beyond ischemic stroke, MSUs have additional clinical and research applications that can profoundly impact other cohorts of patients who require time-sensitive neurological care.
Keywords: acute stroke; thrombectomy; thrombolysis; prehospital; emergency neurology